Comparative Analysis of Lighting Elements’ Effects on Electric System - TERZİ, ÜMİT KEMALETTİN (My University, 2021)
Due to the increase of demand for energy requirement, and the decrease of energy sources day by day, it is being understood that it is required to efficiently use the energy sources in order to ensure the balance of demand for electric energy. The lighting elements use about 1/5 of the electric energy produced in our country. Especially while selecting the lamps with high energy efficiency, it is important to consider the circumstances which may create negativities such as harmonics, power factor, crest factor, inrush current, and flicker effect in terms of quality of power. Moreover, impurity which may occur in the network affects the other devices negatively. In this study, the quality of power of lighting elements of more than one type was examined in detail. In the experiments, technical analyses were performed by the use of 13 different lighting elements extensively used in our country at site, factory, and domestic environments, and they were evaluated in terms of their positive and negative effects on the network.
Keywords: Quality of power; lighting elements; harmonics; crest factor; inrush currents; flicker effect